Are Urbanites More Permissive? Germany's Urban Geography of Prejudice. (November 2014) - Dirksmeier, Peter
Traditionally, bowing to the migration history of Germany, larger proportions of foreigners live in major German cities than in other parts of the country. According to contact theory, famously developed by social psychologist Gordon Allport in the 1950s, intergroup contacts between different ethnic groups reduce prejudice. The main aim of the article is to examine whether the level of prejudice toward foreigners is lower among the German urban population due to greater contact opportunities and habituation among different ethnic groups in Germany's major cities, which reduces prejudice as well. The presented findings show, first, that prejudice is only slightly lower in the major cities. Second, this finding crucially depends on the quality of contacts. Only friendships between Germans and foreigners show a significant impact on reducing prejudice. Clearly, beyond the level of acquaintance with individual members of an out-group, only voluntary contacts are able to diminish prejudice. Third, in terms of spatial context effects, the switch between majority and minority group positions in residential areas appears to be a tipping point for prejudice, which means that even people with low levels of prejudice wish to live as the ethnic majority in their respective residential area.